Data Acquisition Prototype Chamber of Mechanical Seals Test Plant API-682 Using NI MY-RIO - Sumardi, Adhitya; Lilansa, Noval; Rifai, Afaf Fadhil; Iman, Fachri; Nursyam, M.; Sari, Yunita Indah (Politeknik Ganesha Medan, 2019)
— Seal Chamber in Mechanical Seal Test Plant is a part that is used for heat exchange between hot liquid fluid in the form of condensed steam and cold liquid fluid in mechanical seal test plant. In heat exchange it is arranged so that the hot fluid can raise and lower the temperature from 20 ℃ to 80 ℃ and vice versa within 1-2 minutes. In the exchange of heat, data acquisition is still needed, which is then processed by data acquisition software that has been calibrated to determine the sensor response to the environment for test plant. In this study, data acquisition and monitoring systems were carried out and multi tasking synchronization with several sensors with one centralized controller. In addition, the volume seal chamber is equipped with a valve regulated by a servo motor to regulate the amount of hot liquid fluid in the form of condensed steam. Valve is used to be a regulator of the flow of hot fluid that enters and exits the seal chamber volume model. This research will be used to control the level and temperature in prototype of the Mechanical Sil test plant according to API 682. The manual control is done and there is an average error for the relationship of the actual valve with the water flow sensor of 8.42%.